The impact of body composition and fat distribution on blood pressure in young and middle-aged adults - Zhao, Song; Tang, Jiamin; Zhao, Yifan; Xu, Chong; Xu, Yawei; Yu, Shikai; Zhang, Yi (Frontiers in Nutrition, 2022)
Background The relative contributions of each component of body composition to blood pressure (BP) remain unclear. Objective We aimed to comprehensively investigate the impact of body composition and fat distribution on BP and quantify their relative contributions to BP in a large cohort with young and middle-aged adults. Methods 14,412 participants with available data on whole-body DXA measurement from the National Health and Nutrition Examination Survey were included. Multiple stepwise linear regressions of BP on components of body composition and fat distribution were built. Then, relative importance analysis was performed to quantify the contributions of each component to BP. Results The median age of participants was 36 years and there were 50.7% women. Linear regression with mutual adjustment showed that total fat mass, total muscle mass, and trunk fat mass significantly and positively associated with BP; however, arm and leg fat mass significantly and negatively associated with BP. In men, after further adjusted for potential covariates, SBP were significantly determined by trunk fat mass (β = 0.33, P < 0.001), leg fat mass (β = − 0.12, P < 0.001), and total muscle mass (β = 0.10, P < 0.001); and DBP were significantly determined by trunk fat mass (β = 0.52, P < 0.001), leg fat mass (β = −0.15, P < 0.001), arm fat mass (β = −0.23, P < 0.001), and total muscle mass (β = 0.06, P < 0.001). Similar results were observed in women. Relative importance analysis showed that trunk fat mass was the major contributor (38–61%) to both SBP and DBP; meanwhile, total muscle mass also made relatively great contribution (35–43%) to SBP. Conclusion Both fat mass and muscle mass independently associated with and substantially contributed to SBP in both men and women. After full adjustment, trunk fat mass positively associated with both SBP and DBP, and was the most dominant contributor to BP; however, leg fat mass negatively associated with both SBP and DBP.